The Relationship of Knowledge and Parents’ Attitudes with Children’s Potty Training in Gampong Ujong Drien - Fitrah Reynaldi; Safrizal Safrizal; Yarmaliza Yarmaliza; Teungku Nih Farisni; Fitriani Fitriani; Zakiyuddin Zakiyuddin; Darmawi Darmawi (Universitas Teuku Umar, 2019)
One of the ideals of a nation is to produce a healthy and smart generation. Good generations in the future are formed from the first 1000 days of life to the age of 5 years. An important stimulus is to foster a child's independence in urinating and defecating in the toilet. The strategy that can be done by parents in teaching their children BAB and BAK is through potty training. The purpose of this study was to determine the relationship of knowledge and attitudes with potty training in under three years child’s. This research is analytic with cross sectional design. A sample of 40 toddler parents were taken using the total population technique. Chi Square test the relationship of parental knowledge with potty training obtained P Value 0.002 <0.05 so that parental knowledge with the implementation of potty training has a significant relationship. Chi Square test the relationship between parental attitudes with potty training obtained P Value 0.004 <0.05 so that parental attitudes with the implementation of potty training have a significant relationship. The conclusion of this study is that knowledge and attitudes have a significant relationship with potty training in under three years child’s. It is recommended to the Puskesmas to make an introduction to potty training programs for parents so that the implementation of potty training can be achieved optimally.